Conjugated linoleic acid of dairy foods is affected by cows’ feeding system and processing of milk - Ruiz,Juan Pablo Avilez (2016)
ABSTRACT The distribution of conjugated linoleic acid (CLA) in dairy products commercially available in Chile is poorly understood. This study aimed to assess the content of CLA in dairy cow products from Chile and the effect of processing fresh milk into dairy products. Samples of raw milk were categorized into two groups based on the animal feeding system utilized by the dairy farm: 1) grazing based systems (Los Lagos region); and 2) housing systems using total mixed ration (TMR) diets (Los Angeles region). Simultaneously, commercial samples of condensed milk, powdered milk, butter and Gouda cheese were analyzed. Furthermore, samples of raw milk and processed products (powdered and sweetened condensed milk) were also analyzed. Dairy farms based on grazing systems had higher levels of CLA in raw milk than TMR farms. In addition, average values of CLA were 1.72 g 100 g−1 of total fatty acids, in spring milk in the Los Lagos region, and 0.42 g 100 g−1 in summer milk, in the Los Angeles region. Similarly, the CLA content of dairy products was higher than that of raw milk. Milk processing affected the transferring of CLA from fresh milk into the final products. Sweetened condensed milk presented lower CLA values than raw and powdered milk. In conclusion, this study indicates the importance of the production systems to the CLA content as well as the effects of milk processing into dairy products. To sum up, more research is needed to elucidate the exact effect of the processing conditions of dairy products on the CLA content.